Działalność Aleksandry Kołłontaj w świetle publikacji szwedzkiego dziennika „Dalpilen. Tidning för Falu län och stad” (1915–1926) - Ratuszniak, Jan (Acta Universitatis Lodziensis. Folia Historica, 2014)
The image of Alexandra Kollontai activity wasn’t placed in the magazine „Dalpilen”. The office of the newspaper was definitely conservative, but surprisingly new social groups coming into existence in Sweden became emancipated and demanded their laws. Journalists for this newspaper tried to fight as amended with the feather. The office of „Dalpilen” was not interested Alexandra Kollontai and her connections with Sweden before the World War I. It could result from the provincialism of the newspaper. Only discussion in the contemporary press and numerous addresses of socialists objecting to the arrest and the left-wing deportation activists forced „Dalpilen” to the reaction. They joined in the campaign of right-wing media being aimed at a discredit then Kollontai and her friends. In the next article about Kollontai Russian sympathy for promoters of the disarmament journalist of „Dalpilen” criticised activity of the left-wing activist in Norway and accused Kollontai also for being a spy of the tsarism. According to the version from Falun pacifist passwords delivered by her were supposed to serve making Scandinavian countries defenceless before the invasion of Russians. „Dalpilen” didn’t write about Alexandra Kollontai through a few years. Only in 1925 when she reignited from the ambassadorship journalists from Falun wrote about Kollontai. In the article Liberation from communist embrace she was a symbol the USSR in Norway which steered the local left hand of the political landscape. Her defeats editors accepted „Dalpilen” with joy. The image of Kollontai in newspaper „Dalpilen” evolved from the tsarist agent for the woman – of ambassador supervising Norwegian communists. To this image stereotypes made up to the subject of Russia and discrediting Swedish socialists. One should however underline, that since the newspaper from Falun concentrated on domestic and Scandinavian matters, of information about the author of the Love of worker bees it was little. Her as the supporting figure were usually being put in texts, they took a stance for her cooperation with Bolsheviks, not treating her as the socialist standing up for women’s rights.